There Is No Association Between the Number of Stent Retriever Passes and the Incidence of Hemorrhagic Transformation for Patients Undergoing Mechanical Thrombectomy - Hassan, Ameer E.; Kotta, Hari; Shariff, Umar; Preston, Laurie; Tekle, Wondwossen; Qureshi, Adnan (Frontiers in Neurology, 2019)
Background: Previous research has focused on the association between hemorrhagic transformation (HT) incidence and pre-procedural variables (i.e. baseline variables) rather than the association between HT incidence and endovascular treatment (EVT) procedural variables (e.g. stent retriever passes). Objective: To assess the association, if any, that exists between the number of stent retriever passes per procedure and the incidence of HT for patients undergoing mechanical thrombectomy. Methods: An endovascular database from a comprehensive stroke center was used to collect data on EVT patients treated with Trevo, Solitaire, or Penumbra stent retriever from the years 2012-2017. Statistical analyses were conducted on the stent retriever passes, demographics, morbidities, medication usage, and outcomes and their association with HT. Results: Of the 329 total patients, 46 (14%) had HT. The HT group had an average [SD] of 1.65[0.67] and range of [1-3] passes per procedure while the non-HT group had an average[SD] of 1.63[0.86] and range of [1-5] passes per procedure. Admission NIHSS score (p=0.0003) and the incidence of diabetes mellitus (DM) (p=0.05) were significantly higher in the HT group. Subdividing HT into symptomatic and asymptomatic ICH groups failed to display significant differences in the distribution of the stent retriever passes (p= 0.969). The number of passes failed to show any association with HT (p=0.804) while admission NIHSS score was found to have an OR of 1.07 (95%CI: 1.029-1.121,p=0.001) with HT incidence. Conclusion: No significant association was found between HT incidence and the stent retriever passes. Further multicenter studies are warranted to corroborate our results.